Accounting for qualification in mismatch unemployment - Anja Bauer (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2023)
This paper shows the evolution of mismatch unemployment over the period from 2007 to 2022 in Germany. A substantial part of mismatch unemployment results from a misallocation on the qualification level rather than on the occupational level. Taking the qualification level into account, an upward trend in mismatch unemployment in the aftermath of the COVID-Crisis emerges that raises the share of mismatch unemployment in total unemployment about 3 percentage points in comparison the pre-COVID level. Furthermore, I can show that the COVID-Crisis had a different impact on the occupation-qualification level than the Global Financial Crisis. In a nutshell, the COVID-crisis hit especially the labor market for unskilled and semi-skilled workers. – – Dieses Papier zeigt die Entwicklung der Mismatch-Arbeitslosigkeit in Deutschland im Zeitraum von 2007 bis 2022. Ein wesentlicher Teil der Mismatch-Arbeitslosigkeit resultiert aus einer Fehlallokation auf der Qualifikationsebene und nicht auf der beruflichen Ebene. Unter Berücksichtigung des Qualifikationsniveaus zeigt sich ein Aufwärtstrend der Mismatch-Arbeitslosigkeit nach der Covid-Krise, der den Anteil der Mismatch-Arbeitslosigkeit an der Gesamtarbeitslosigkeit um etwa 3 Prozentpunkte über dem Vor-Krisen-Niveau liegt. Zudem hatte die Covid-Krise einen anderen Einfluss auf das Berufsqualifikationsniveau als die globale Finanzkrise. Zusammenfassend lässt sich sagen, dass die Covid-Krise vor allem den Arbeitsmarkt für un- und angelernte Arbeitskräfte getroffen hat.
Keywords: E24; J6; 330; allocation; job finding rate; mismatch; occupation